Total Synthesis and Biological Evaluation of Sericetin for Protection against Cisplatin-Induced Acute Kidney Injury - Kim, Eun Sun; Jang, Hongjun; Chang, Sun Young; Baek, Seung Hoon; Bae, Ok Nam; Kim, Hyoungsu (Journal of Natural Products, 2018)
A concise synthesis of sericetin (1) was performed in four steps from readily available 3-O-benzylgalangin (4), featuring electrocyclization to produce the tricyclic core and a sequential aromatic Claisen/Cope rearrangement to incorporate the 8-prenyl group of 1. In addition, the therapeutic potential of sericetin (1), isosericetin (2), and three prenylated tetracyclic synthetic intermediates (11, 12, and 14) against cisplatin-induced nephrotoxicity using renal tubular cells were evaluated. Compound 14 showed therapeutic potential against cisplatin-induced kidney damage.
Keywords: Acute Kidney Injury; Animals; Cell Line; Cisplatin; Fabaceae; Molecular Structure; Protective Agents; Rats; Rats, Sprague-Dawley